The EU-CELAC partnership and the revision of the concept of multilevel inte-regionalism - Ayuso, Anna (2016)
The birregional strategic partnership between the EU and LAC initiated in 1999, has evolved to adapt to both; changes in the global context and the restructuring of power, and changes in regional integration processes that have altered the balance and nature of the relationship. Currently the EU and LAC have multiple levels of relationship - inter-regional, trans-regional and sub-regional - comprising a heterogeneous set of actors in a complex interregionalism scheme, surpassing the traditional categories of the studies on nterregionalism.